Procedimiento para la planeación agregada en la pequeña y mediana industria manufacturera - Torres Acosta, Jairo Humberto (Ingeniería, 2000)
The investigation work was developed taking like reference mark the state of the art on the Aggregate production Planning in the universal context and in the South American context, to end up studying to depth the behavior of the Colombian productive culture regarding the Gliding, the Programming and the Control of the production, in particular, the development level in the investigation and the application reached in the PYME (Small and Medium Company) in the specific field of the Aggregate production Planning, working in agreement with the government politicians about productivity and competitiveness, as well as in the observation about the necessity of to develop and to apply appropriate proceduresfor the sector manufacturer and the benefits that these they will generate in the Colombian economic and social context. For the position of the procedures one kept in mind, besides the state of the art in Aggregate production Planning, precedent works developed by the author, as well as their professional activity in the consultancy field, that which allowed to visualize the existent problem in the PYME. It is as well as you arrives to the position of a procedure for the Aggregate production Planning of Materials, which allows to determine the gross necessities of the different required raw materials during the planning horizon, a procedure for the Aggregate Capacities Planning that generates the gross capacity required in each one of the working sections during the time of planning, and a procedure for the Aggregate Planning of shifts, machines and labor force. These results allow the PYME to have a good support for the taking of decisions in minimum time, that which constitutes a contribution of high novelty and applicability in the Colombian environment. All the outlined procedures were developed making partial applications in different companies of the sector PYME, corroborating this way the coherence of their position so much mathematical as practical. The application of the procedures required the assembly of an appropriate system of information, as well as the development of software for the prosecution of the information and the obtaining of results.